Cytotoxic Granule Trafficking and Fusion in Synaptotagmin7-Deficient Cytotoxic T Lymphocytes - Sleiman, Marwa; Stevens, David R.; Chitirala, Praneeth; Rettig, Jens (Frontiers in Immunology, 2020)
Cytotoxic granules of T lymphocytes (CTL) are derived from the lysosomal compartment. Synaptotagmin7 (Syt7) has been reported to be the calcium sensor triggering fusion of lysosomes in fibroblasts and Syt7 has been proposed to control cytotoxic granule fusion as well. However, release of granzymes persists in the absence of Syt7. To better understand the role of Syt7 in CTL function, we have examined the fusion of cytotoxic granules of CD8+ T-lymphocytes from Syt7 knock-out mice. We have recorded granule fusion in living CTL, using total internal reflection microscopy. Since Syt7 is considered a high affinity calcium-sensor specialized for fusion under low calcium conditions, we have compared cytotoxic granule fusion under low and high calcium conditions in the same CTL. There was no difference in the latency or numbers of fusion events per CTL under low-calcium conditions, indicating that Syt7 is not required for cytotoxic granule fusion. A deficit of fusion in Syt7 KO CTL was seen when a high-calcium solution was introduced. Expressing wild type Syt7 in Syt7 KO lymphocytes reversed this deficit, indicating that it was Syt7-dependent. Mutations of Syt7 which disrupt calcium binding to its C2A domain reduced the efficacy of this rescue. We counted the cytotoxic granules present at the plasma membrane to determine if the lack of fusion events in the Syt7 KO CTL was due to a lack of granules. In low calcium there were no differences in fusion events per CTL, and granule numbers were similar. In high calcium, granule number was similar though wild type CTL exhibited significantly more fusion than Syt7 KO CTL. The modest differences in granule counts do not account for the lack of fusion in high calcium in Syt7 KO CTL. In Syt7 KO CTL expressing wild type Syt7, delivery of cytotoxic granules to the plasma membrane was comparable to that of wild type CTL. Syt7 KO CTL expressing Syt7 with deficient calcium binding in the C2A domain had significantly less fusion and fewer CG at the plasma membrane. These results indicate that Syt7 is involved in trafficking of CG to the plasma membrane.